2017
DOI: 10.3389/fped.2017.00140
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cerebral and Renal Oxygenation Status during Neonatal Digestive Surgeries Using Near Infrared Spectroscopy

Abstract: BackgroundDepending on the initial pathology, hypovolemia, intra-abdominal hypertension, and sepsis are often encountered in neonatal digestive surgery. Accurate newborn monitoring during and after surgery is essential to adapt resuscitation protocols. Near infrared spectroscopy (NIRS) is non-invasive and can detect hypoperfusion which indicates a low circulatory blood flow, regardless of the cause.ObjectiveEvaluating changes in cerebral and renal regional oxygen saturation during neonatal digestive surgeries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…89 In contrast to the technologies described above, NIRS is an indirect optical imaging modality because it does not provide direct visualization of the microvasculature. The main organs interrogated with NIRS are the brain and skeletal muscle, [90][91][92] although it has also been used to image the adult bladder, 93 pediatric kidneys, 94,95 abdominal/mesentery, 95,96 and liver. 97 For NIRS imaging, oxyhemoglobin (HbO2) and deoxyhemoglobin (Hb) are the dominant chromophores in human tissue that dynamically change over time.…”
Section: Op Tic Al Imag Ingmentioning
confidence: 99%
“…89 In contrast to the technologies described above, NIRS is an indirect optical imaging modality because it does not provide direct visualization of the microvasculature. The main organs interrogated with NIRS are the brain and skeletal muscle, [90][91][92] although it has also been used to image the adult bladder, 93 pediatric kidneys, 94,95 abdominal/mesentery, 95,96 and liver. 97 For NIRS imaging, oxyhemoglobin (HbO2) and deoxyhemoglobin (Hb) are the dominant chromophores in human tissue that dynamically change over time.…”
Section: Op Tic Al Imag Ingmentioning
confidence: 99%
“…Nineteen studies used NIRS. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Fourteen of these measured only cerebral oxygenation and five combined cerebral oxygenation with cerebral blood flow (CBF) or cerebral autoregulation (Table 1). Five studies used aEEG -in four to measure cerebral activity [33][34][35][36] and in one, a large cohort study, to detect epileptic activity only (Table 2).…”
Section: Structured Literature Searchmentioning
confidence: 99%
“…Near-infrared spectroscopy: correlations with other physiological variables In the five studies that reported a decrease of cerebral oxygenation, three reported no significant changes in blood pressure (BP) 15,16,27 and two did not report BP values. 24,28 In the four studies that reported an increase in Copyright © European Society of Anaesthesiology. Unauthorized reproduction of this article is prohibited.…”
Section: Structured Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations